Współpraca gospodarcza na pograniczu polsko-czeskim po przystąpieniu Polski i Czech do Unii Europejskiej - Adamczuk, Franciszek (Economic cooperation on the Polish-Czech borderland after Polish and Czech Republic accession to the EU, 2006)
The article concerns economic cooperation on the Polish-Czech borderland. This borderland is understood as the llrst belt of 16 poviats on the Polish side and 13 povials on the Czech side. In some cases the scope ofthe research area on the Czech side of the borderland was even wider (second belt of povials and even third one), especially if there were partners from Polish belt which had their Czech partners located outside the first border belt of poviats. Special interest of the research was directed towards the range and forms of communal structures cooperation (cities, communes and adjusting NUTS 2 regions: Lower-Silesian province on the Polish side and on the Czech side besides all Liberecki Kraj and Hradeckralowe Kraj). The article also concerns some problems of euroregional structures on the Polish-Czech borderland. In the end, the author proves that on this borderland, after the accession of both the countries to the EU, the range and intensification of cooperation considerably extended. There still appear new forms of economic cooperation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 63-71